STUDYING CASPIAN SHAD (ALOSA CASPIA CASPIA) DIET IN SOUTHWEST COASTAL AREA OF THE CASPIAN SEA, GUILAN PROVINCE WATERS - H. Abdollah porbiria; K. Abbasi; A. Keyvan; J. Sabkara (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2006)
Little is known about the biological characteristics of the Caspian shad, a commercial fish of Clupeidae family living in the Caspian Sea. Monthly random samples of the fish were collected at the Guilan province shores, southwest of the Caspian Sea from October 2001 to August 2003. Beach seine and gill nets were used in the sampling. Food items, condition factor and feeding changes with the change in the fish age, sex, station and season after invasion of Ctenophore Mnemiopsis leidyi to the Caspian Sea were studied. Samples (n= 262) had fork length 88-235 (156.7±31.9) mm, weighed 8-196 (51.92±32.7) grams and aged 1-6 (2.81±0.9) years old. The Vacuity Index (CV), Intestinal Relative Length (RLG) and Index of Fullness (IF) of the specimens were determined as 10.3%, 0.52±0.03 and 102.9±114.5, respectively. Phytoplankton (specially Rhizosolenia and Spirogyra) comprised 1.8%, zooplanktons (Ostracoda, Rhizopoda, Cladocera, Rotatoria, Copepoda, Cirripedia, Mysidacea, Bivalvia larvae and bony fishes larvae and eggs) comprised 98.0% and benthic fauna (Foraminifera, Porifera, Cumacea, Amphipoda, insects larvae and Palaemonidae) comprised 0.2% of the food abundance in the fish stomach and intestine. Among the food items, orders Copepoda (Acartia spp.) and Cirripedia (cypris Balanus) were the mainfood, comprising 83.1 and 12.9% of abundance, respectively. Acartia comprised 97.3, 80.4, 48.0 and 68.3% of the food in autumn, winter, spring and summer, respectively. For cypris Balanus, these figures were 2.0, 2.6, 41.9 and 25.3% for the seasons. No significant difference was found in food diversity and its abundance between male and female fish and between different ages. Generally, Acartia spp. and Balanus were dominant food items in the male and female fish and in different sized specimens. Acartia comprised about 97.0% of the food abundance in Talesh and Kiashahr areas and 65.7%in Anzali shores. The zooplanktons, as the main food item of the fish have suffered a major decrease due to the invasion of Mnemiopsis leidyi to the southern Caspian Sea. Hence, the index of fullness (IF) and growth of the fish shows a great reduction recently.